Adubação organomineral em mandacaru (Cereus jamacaru P. DC.) com espinho nas condições do semiárido da Paraíba - Leite, Arliston Pereira (2017)
The mandacaru (Cereus jamacaru P. DC.) Is a native species of the caatinga vegetation, belonging to the family Cactaceae. Mandacaru behaves like a species of great potential for recovery of areas in potential of degradation, mainly for presenting high capacity of Resistance to rainfall environments, as well as providing food and shelter for different types of species. A review of the history of the species, the importance of mandacaru for the semi arid region, alternatives for mandacaru use, physical and morphological aspects, cropping systems and types of fertilization that can be used in cultivation are presented. Five treatments were used, composed of two types of manure (bovine and goat) and a fertilization with triple super phosphate to evaluate morphological and physiological aspects of mandacaru. The influence of different fertilizations on height, diameter, spine color, pH, temperature, number of shoots, flowers and fruits were evaluated. The vegetative part of the mandacaru was planted, the cladodes were cut of two matrices selected and close. The cladodes were cut with 50 cm in length and after cutting placed in a shed for 15 days for a healing period. After this period the cladodes were planted in the field in pits of 20 cm of depth previously fertilized. Cultural treatments such as crowning, weeding and irrigation were carried out to fix the seedlings. The experimental plots were subdivided in time. The data of the evaluations were submitted to the analysis of variance to verify the significance of the interactions between the treatments applied and the evaluation periods for the height variable, the other variables were tested by the Tukey test with the SAS® statistical program. There were interaction of the treatments with the evaluation periods for height, treatments with cattle manure and control had the lowest mortality rates, for the other variables no statistical differences were found for the parameters evaluated in relation to the treatments applied. Fertilization with bovine and goat manure in addition to phosphate did not interfere with the growth of cladode, temperature and pH. The water scarcity in the region may be a factor that has interfered in these results.